Upaya Peningkatan Perilaku Ibu Postpartum Melalui Edukasi Family Centered Maternity Care (Fcmc) Tentang Perawatan Masa Postpartum di Wilayah Kerja Puskesmas Gambirsari Surakarta - Desy Widyastutik; Ernawati Ernawati; Erinda Nur Pratiwi; Retno Wulandari (Jurnal Salam Sehat Masyarakat (JSSM), 2021)
The role of a parent cannot be separated from the participation or cooperation between the mother and the family (husband) and other family members. Barriers that are still found in the care of postpartum mothers are the perception of the community that post partum mothers are sick mothers, their mobility is inhibited, their diet is restricted, colostrum breastfeeding is inhibited so that the needs of post partum mothers are prioritized for full rest. The involvement of extended families in infant care has so far been misunderstood, where baby care is left to other family members. After efforts to improve the behavior of postpartum mothers through Family Centered Maternity Care (FCMC) education, it is hoped that postpartum mothers can carry out postpartum care by involving their families. Implementation method with demonstration and discussion. The media used are baby phantoms, postpartum care booklets, LCDs, laptops and projectors. The implementation of health education is carried out by home visits by paying attention to health protocols from March 2020 to September 2020. The result of community service is that 90% of postpartum mothers can provide postpartum care with family involvement. And from the results of monitoring and evaluation by means of meeting again by means of home care to postpartum mothers using instruments related to postpartum care. Based on the implementation of community service, it can be concluded that there is an increase in the behavior of postpartum mothers in postpartum care in the Gambirsari Public Health Center, Surakarta.